Identifikasi Alih Fungsi Lahan Pertanian dan Kondisi Sosial Ekonomi Masyarakat Desa Karangwidoro Kecamatan Dau Kabupaten Malang - Abd Haris; Lutfi Bagus Subagio; Fajar Santoso; Neni Wahyuningtyas (Media Komunikasi Geografi, 2018)
Abstract Land is a strategic resource that has value economically. Currently, the amount of agricultural land annually continues to decrease. The reduced number of agricultural land is the result of an increase in the number and activity of the population and development activities. The research method used in this research is qualitative. This study attempts to examine the conversion of agricultural land and its impact on the socio-economic conditions of the communities of Karangwidoro Village. Based on the results of the research note that land transfer function in Karangwidoro Village including the type of massive transfer of functions. Almost all kawsan Karangwidoro village is now a settlement, whereas previously a farming area. The area of land that has been transformed into housing from 2003 to 2017 is approximately 193 hectares. As a result of the conversion of agricultural land into housing makes the people of Karangwidoro Village experiencing the transition of livelihood or commonly referred to as economic transformation.Keywords: Land Functionality Transfer, Agriculture, Social, Karangwidoro Abstrak Tanah merupakan sumberdaya strategis yang memiliki nilai secara ekonomis. Saat ini, jumlah luasan tanah pertanian tiap tahunnya terus mengalami pengurangan. Berkurangnya jumlah lahan pertanian ini merupakan akibat dari adanya peningkatan jumlah dan aktivitas penduduk serta aktivitas pembangunan. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif. Penelitian ini berupaya untuk mengkaji alih fungsi lahan pertanian dan dampaknya terhadap kondisi sosial ekonomi masayarakat Desa Karangwidoro. Berdasarkan hasil penelitian diketahui bahwa Alih fungsi lahan di Desa Karangwidoro termasuk jenis alih fungsi yang masif. Hampir seluruh kawsan Desa Karangwidoro saat ini menjadi pemukiman, padahal sebelumnya merupakan kawasan pertanian. Luas lahan yang berubah menjadi perumahan sejak 2003 hingga 2017 kurang lebih sekitar 193 hektar. Akibat alih fungsi lahan pertanian menjadi perumahan menjadikan masyarakat Desa Karangwidoro mengalami peralihan mata pencaharian atau biasa disebut dengan istilah transformasi ekonomi.Kata kunci: Alih Fungsi Lahan, Pertanian, Sosial, Karangwidoro